2002
DOI: 10.1152/ajpendo.00425.2001
|View full text |Cite
|
Sign up to set email alerts
|

Integrated effects of multiple modulators on human liver glycogen phosphorylasea

Abstract: Hepatic glucose production is increased in people with type 2 diabetes. Glucose released from storage in liver glycogen by phosphorylase accounts for ϳ50% of the glucose produced after an overnight fast. Therefore, understanding how glycogenolysis in the liver is regulated is of great importance. Toward this goal, we have determined the kinetic characteristics of recombinant human liver glycogen phosphorylase a (HLGPa) (active form) and compared them with those of the purified rat enzyme (RLGPa). The Michaelis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 70 publications
4
43
1
Order By: Relevance
“…In liver, high-dose AICAR stimulates glycogenolysis (25,26) but also inhibits gluconeogenesis (31,57), lipogenesis, and cholesterol synthesis (23,35). However, enhanced glycogenolysis in muscle (32) and liver (8,22) and suppressed hepatic gluconeogenesis (31) can both be induced allosterically in vivo by raised intracellular levels of ZMP independently of a direct AMPK effect. In the most recent studies employing low-dose AICAR, HGP was enhanced in the presence of low-and high-dose insulin at eu-and hyperglycemia (8,9,38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In liver, high-dose AICAR stimulates glycogenolysis (25,26) but also inhibits gluconeogenesis (31,57), lipogenesis, and cholesterol synthesis (23,35). However, enhanced glycogenolysis in muscle (32) and liver (8,22) and suppressed hepatic gluconeogenesis (31) can both be induced allosterically in vivo by raised intracellular levels of ZMP independently of a direct AMPK effect. In the most recent studies employing low-dose AICAR, HGP was enhanced in the presence of low-and high-dose insulin at eu-and hyperglycemia (8,9,38).…”
Section: Discussionmentioning
confidence: 99%
“…Such pharmacological doses would raise tissue levels of muscle ZMP to that of a direct ZMPallosteric stimulation of key intracellular enzymes of glucose metabolism (22,32,45), in addition to allosteric activation of AMPK (18). AICAR appears to activate AMPK by an allosteric ZMP-directed mechanism and not directly by activation of its upstream AMPK kinase (60).…”
Section: Impact Of Low-dose Aicarmentioning
confidence: 99%
“…In the cell, the adenine nucleotides ATP, ADP, and AMP are tied directly or indirectly to all energetic pathways and allosterically control numerous regulatory enzymes (2)(3)(4)(5)(6). Changes in adenine nucleotides typically occur such that ATP and AMP deviate in reciprocal directions, while ADP remains constant (1).…”
Section: Introductionmentioning
confidence: 99%
“…Net glycogen deposition depends on the activities of glycogen synthase and phosphorylase. The activities of these enzymes are regulated not only via phosphorylation/dephosphorylation but also allosterically by some metabolic intermediates (6,17,19). The effects of fructose administration on phosphorylase activity are controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Kaufmann and Froesch (27) showed an inhibition of phosphorylase by fructose 1-phosphate. ErcanFang et al (17) reported that phosphorylase was directly inhibited by high concentration of fructose 1-phosphate but not by physiological levels of the sugar. There is no evidence that glycogen synthase activity is regulated directly by changing fructose 1-phosphate content (concentration).…”
Section: Discussionmentioning
confidence: 99%